EVIDENCE-BASED MEDICINE: THE SCIENTIFIC METHOD AS A LIGHT IN THE DARKNESS OF NEGATIONISM - Pedro Biasi Toson, João; Pereira Rezende, Isadora (Health and Society, 2022)
This article analyzes the potential problems of denialism in the field of health, based on some practical examples, such as the case of the anti-vaccine movement, particularly aggravated by the Covid-19 pandemic, and the use of fake news during the pandemic. of Covid-19 in Brazil, with a parallel between what happened in the anti-retroviral movement in South Africa, and the appearance of the scientific method as a form of combat. A fighting action model suggests that South Africa’s use of antiretrovirals for antiretroviral treatment for HIV caused more than 300,000 deaths between 1999 and 2007. Here, to mitigate the results of denialism . For this, a literature review was carried out. Global analytical studies are toned down and problem-based medicine can contribute to making political movement necessary, more effective against such a phenomenon.